Development and Validation of the Modified Charlson Comorbidity Index in Incident Peritoneal Dialysis Patients: A National Population-Based Approach. Issue 1 (January 2017) - Cho, Hyunjeong; Kim, Myoung-Hee; Kim, Hyo Jin; Park, Jae Yoon; Ryu, Dong-Ryeol; Lee, Hajeong; Lee, Jung Pyo; Lim, Chun-Soo; Kim, Kyoung Hoon; Oh, Kook-Hwan; Joo, Kwon Wook; Kim, Yon Su; et al.
Background: The utility of applying the Charlson comorbidity index (CCI) to peritoneal dialysis (PD) patients is disputed because the relative weight of each comorbidity in PD patients may be different from those in other chronic diseases. We aimed to develop and validate a modified CCI in incident PD patients (mCCI-IPD) for better risk stratification and prediction of mortality. Methods: The mCCI-IPD was developed using data from all Korean adult incident PD patients between 2005 and 2008 ( n = 7, 606). Multivariate Cox regression was used to determine new weights for the individual comorbidities in the CCI. The prognostic performance of the mCCI-IPD was validated in an independent cohort ( n = 664) through c -statistics and continuous net reclassification improvement (cNRI). Results: A total of 75.5% of the patients in the development cohort had 1 or more comorbidities. The Cox proportional hazards model provided reassigned severity weights for the 11 comorbidities that significantly predicted mortality. In the validation cohort, the CCI and mCCI-IPD scores were both correlated with survival and showed no differences in their c -statistics. However, multivariate analyses using cNRI revealed that the mCCI-IPD provided a 38.2% improvement in mortality risk assessment compared with the CCI (95% confidence interval [CI], 15.3 – 61.0; p < 0.001). These significant reclassification improvements were observed consistently in subjects with events (cNRIEvent, 28.2% [95% CI, 6.9 – 49.5; p = 0.009]) and without events (cNRINon-event, 10.0% [95% CI, 1.7 – 18.2; p = 0.019]). Conclusions: Compared with the CCI, the mCCI-IPD showed better performance in mortality prediction for incident PD patients. Therefore, this tool may be used as a preferred index for statistical analysis and clinical decision-making.